Sapi-Sapian, Contextualizing Mathematical Concepts Through Cultural Tradition - Widyasari Widyasari; Rachmaniah Mirza Hariastuti (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
Sapi-sapian is one of the traditions in Kenjo Village which is carried out every Muharram month as an expression of gratitude to God for abundance of agricultural crops. Sapi-sapian tradition contains four processions, namely the selametan pecel gerang, tumpeng serakat, ider bumi oncor-oncoran,and the celebration, which contain ethnomathematics. In order to get the most out of ethnomathematics in the Sapi-sapian tradition, a qualitative-descriptive study was conducted as a method. Due to the conditions of the Covid-19 pandemic which caused the Sapi-sapian tradition to be carried out optimally in 2020, data was collected using in-depth interviews, and cultural documentation. The research informants were the Chief of the Kenjo Village Custom, the Deputy Head of the Adat, and one resident who had been involved in the implementation of the Sapi-sapian tradition. The data obtained were analyzed qualitatively based on several analysis processes in ethnographic research. The results showed that there are mathematical concepts found in the Sapi-sapian tradition of Kenjo Village, including : two and three dimensional geometry, fractions, transformations, and traditional measurements with non-standard units. Keyword : Sapi-sapian, Cultural tradition, Ethnomathematics